Impact of teleworking and remote work on business productivity, retention, advancement, and bottom line - Chandan, Harish C. 1947- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series, 2024)
"This book delves into the multifaceted impact of teleworking on businesses, exploring how different organizations grapple with these challenges, drawing on the experiences of industry giants like Google and IBM"--